Detection of fungal pathogens by a new broad range real‐time PCR assay targeting the fungal ITS2 region. Issue 10 (October 2017) - Schabereiter‐Gurtner, Claudia; Zeller, Iris; Mihalits, Verena; Selitsch, Brigitte; Barousch, Wolfgang; Hirschl, Alexander M.; Makristathis, Athanasios; Willinger, Birgit
Abstract : Purpose. : The rise in the incidence of fungal infections and the expanding spectrum of fungal pathogens make early and broad detection of fungal pathogens essential. In the present study, a panfungal real‐time PCR assay for the broad‐range detection of fungal DNA (Fungi assay) in a wide variety of clinical specimens was developed. Methodology. : Our in‐house, HybProbe real‐time PCR assay targets the ITS2 region of fungal DNA. The applicability was evaluated by testing 105 clinical samples from 98 patients with suspected fungal infection. Samples included tissue biopsies, paraffin embedded tissues, aspirates, EDTA‐anticoagulated blood, cerebrospinal fluids and bronchoalveolar lavages. Results. : Fungal pathogens were identified by the Fungi assay in 47 samples. In all of these cases, conventional methods and clinical data were also indicative for a fungal infection. Five samples were interpreted false negative. blast analyses of the amplicons derived from 11 samples revealed the presence of environmental fungal species while other tests and clinical data did not suggest a fungal infection. This fact might indicate contaminated samples. The remaining 42 samples were negative by the Fungi assay as well as the conventional methods and were therefore regarded as true negatives. Thus, sensitivity was 90.4% and specificity 79.2 %. Conclusion. : The Fungi assay improved the targeted diagnosis of fungal infections allowing pathogen identification in samples that were histologically positive but culture negative. For reliable diagnosis, results have to be interpreted in context with conventional methods and clinical data.